Analysis of State Policy Towards the Citizenship Status of Families Sympathizing with ISIS According to International Law - Desi Natalia Sihombing; Djayeng Tirto; Arifuddin Uksan; Achmed Sukendro; Herlina Juni Risma Saragih; Pujo Widodo (Formosa Journal of Social Sciences (FJSS), 2024)
The importance of an individual's citizenship status has led the international community to establish several legal instruments related to citizenship status. The right to renounce citizenship is based on the principle that individuals have the right to determine their own citizenship, subject to the reasonable requirements of the laws of the involved states. This research method employs a qualitative approach, focusing on examining the application of legal norms and principles to legal theories and doctrines. This involves identifying the policies of various states regarding the citizenship status of families who sympathize with ISIS. Consequently, the research aims to formulate policy considerations of states concerning international legal provisions